Impact of yeast supplementation derived from dried banana residue on performance, egg quality, intestinal health, and feed cost in laying hens - Suphawadee Yaemkong; Tossaporn Incharoen; Norakamol Laorodphan; Punnares Rattanapradit; Panit Yamchuen; Touchkanin Jongjitvimol (Cogent Food & Agriculture)
Dried banana residue, a by-product of banana processing, holds potential as a valuable feed supplement for poultry. However, despite efforts to repurpose agricultural by-products, remnants from dried banana processing remain largely untapped. This study aimed to assess the potential of yeast derived from dried banana residue as a feed supplement for laying hens, evaluating its impact on performance, egg quality, small intestinal morphology, intestinal bacterial population, and feed cost. Sixty 17-week-old commercial layers were divided into two groups, with each group receiving either a control diet or a diet supplemented with yeast from dried banana residue. Over 90 days, no statistically significant differences (p > 0.05) were found in feed intake, egg production, feed conversion ratio, egg weight, egg mass, and egg quality traits between the groups. However, the yeast-supplemented group exhibited significantly higher villus height and a greater ratio of villus height to crypt depth (V:C ratio) in the duodenum compared to the control group (p < 0.05). Additionally, levels of Salmonella sp. in the small intestine were significantly lower in the yeast-supplemented group compared to the control group (p < 0.05). Supplementing the basal diet of egg-laying hens with yeast-fermented banana peels at a 0.1% inclusion level proved beneficial without compromising egg quality. This study highlights repurposing banana processing waste into valuable animal feed, enhancing sustainability, efficiency, and animal health in agriculture. Future research could explore broader applications of yeast from dried banana residue in livestock nutrition across Thailand and the region.